Pengaruh Beban Kerja dan Kompensasi Terhadap Produktivitas Kerja Karyawan PT PLN (Persero) UP3 Makassar Selatan - Wulandari Putri Masri; Syarifuddin Sulaiman; Muhammad Akib (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to analyse the partial effects of workload and compensation on the work productivity of employees at PT PLN (Persero) UP3 South Makassar. A proportional workload and fair compensation are expected to increase employee motivation and work productivity in supporting the achievement of organisational goals. This study uses a quantitative approach with a conclusive research type. Data was obtained through a questionnaire distributed to all employees of PT PLN (Persero) UP3 South Makassar, with 72 respondents using a saturated sampling technique (census). Data analysis was performed using the Partial Least Squares–Structural Equation Modelling (PLS-SEM) method with the assistance of SmartPLS version 4 software. The results of the study indicate that workload has a positive and significant effect on employee productivity, while compensation has a positive and significant effect on employee productivity. The conclusion of this study confirms that proper workload management and appropriate compensation play an important role in increasing employee work productivity.